Social Space Construction of Farmers: A Case Study of Ban Nong Thum, Muang District, Kalasin Province - Wongsaonao, Phra Sanguan (Journal for Developing the Social and Community, 2022)
Social Space Construction of Farmer: A Case Study of Ban Nong Thum, Muang District, Kalasin Province is a qualitative research using conceptual frameworks of social space. It aims to study the adaptation of Ban Nong Thum farmers to the contract agricultural production system and to study the social space construction of ​​Ban Nong Thum farmers. Target group in this research consisted of 20 households of tomato growers in Ban Nong Thum and 3 representatives of entrepreneurs or factories that buy agricultural products, as well as officials and government agencies involved in the produce agricultural products in the area of ​​7 people, including the target group of 30 key informants. The results of this study show that the tomato cultivation model in the contract farming system is a formal production model agriculture is jointly managed between the capital company and the farmer. The company will offer credit in the form of inputs technical knowledge support and farmers will fall into a structure that is at a disadvantage, lack of bargaining power, but farmers did not succumb to the problems that arose. Farmers are fighting adapt to survive with fighting at the individual level in everyday life and a group is formed to create a social space and endeavors to adjust the lifestyles, production methods and social relations between farmers and the capital system, which is expressed in the form of compromise to reduce conflicts and for farmers to survive under contractual production.